EFL students’ motivation on learning English: What can we learn from them? - Yelni Erniyati; Pristian Hadi Putra (Universitas Bengkulu, 2022)
This study aimed to determine the students' motivation of non-English Department—intrinsic and extrinsic—in learning English. It was carried out at the second-grade students of the Quran Science and interpretation study program (IAT) academic year 2020/2021. This study employed descriptive-survey research. There were 34 students becoming the participants of this study. The researchers employed the questionnaire, which consisted of twelve statements to get the data about students’ motivation. it was divided to nine statements about intrinsic motivation and three statements for extrinsic motivation. The data obtained revealed that for intrinsic motivations level, the students were at a high level of motivation with a total mean score of 4. 09 and for extrinsic motivation, the total mean score was 3.97, and it showed that students were also at high level of motivation. Thus, it can be summarized that the students have both intrinsic and extrinsic motivation in studying English although they were non-English Department students. Moreover, the students’ intrinsic motivation in learning English was higher than extrinsic motivation. It can be said that the students were able to control themselves to learn English, even though there was not much external motivation from lecturers or others. Regarding the result of this research, future researchers are expected to conduct depth research related to this topic. Moreover, the English lecturers who teach the students from the non-English department who are motivated should have good techniques and methods in teaching them, in the order they can achieve their goals in learning English.